The Role of Contractual Tax Audit in Calculating Deferred Taxes - A Case Study inthe Audit Firm KPMG - messedad, nour elislam; Announ, Fouad (Journal of Research in Finance and Accounting, 2020)
The study aimed to explore the correlation between tax audit and deferred taxes as well as the divergence between the Algerian financial accounting system and the tax system. Considering deferred taxes as part of the corporate income tax (CIT), we have sought to highlight the tax risk under deferred taxes and its modalities of assessment. In order to test the hypotheses of the research, we conducted a case study in one of the big four consulting firms, namely, KPMG, concluding that the deferred tax concept represents an accounting method as opposed to a tax method. Its purpose is to reinforce the true and fair view of the financial position of companies. Nevertheless, this does not render it risk-free as it can also be used abusively to overstate remittable profits, which according to law is qualified as infringement of foreign exchange regulation, particularly, companies of foreign shareholders operating in Algeria, the violation of which is punishable with severe penalties and fines.